2020
DOI: 10.1002/aenm.202000488
|View full text |Cite
|
Sign up to set email alerts
|

Tomographic Reconstruction and Analysis of a Silver CO2 Reduction Cathode

Abstract: electrochemical CO 2 RR enables direct power-to-X technology, that is the integration of electricity from (intermittent) renewable sources into the formation process of various valuable products. Technoeconomic analyses of CO 2 electrolyzers have identified current density and energy efficiency as the key benchmarks of this technology. [1][2][3][4][5] They further estimate that for adoption of this technology high current densities (hundreds of mA cm − ² or more) are required. The current density of the batch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 35 publications
(41 reference statements)
0
36
0
Order By: Relevance
“…The brighter areas in the backscatter electron image denote heavier elements while the darker regions point to lighter elements. [ 38 ] Therefore, the bright cores and the darker shells/flakes in the backscatter electron image in Figure 3e are attributed to the Zn and carbon, respectively, further depicting the fact that the core–shell Zn@C spheres are closely attached to the surface of carbon flakes.…”
Section: Resultsmentioning
confidence: 94%
“…The brighter areas in the backscatter electron image denote heavier elements while the darker regions point to lighter elements. [ 38 ] Therefore, the bright cores and the darker shells/flakes in the backscatter electron image in Figure 3e are attributed to the Zn and carbon, respectively, further depicting the fact that the core–shell Zn@C spheres are closely attached to the surface of carbon flakes.…”
Section: Resultsmentioning
confidence: 94%
“…McLaughlin et al 58 have recently reported surface area measurements for Ag GDE which are equivalent to a roughness factor of ∼ 50. f r will depend on the properties of the catalyst and the GDL/MPL layer as well as on the deposition technique and the CL thickness.…”
Section: Gmpnp System Of Equationsmentioning
confidence: 99%
“…However, the GMPNP equations are numerically more stable than PNP and do not require additional numerical stabilization for convergence Bohra et al. 43 Lastly, based on the few attempts at measuring the pore structure properties of metal catalysts deposited on GDEs for eCO 2 R, 22,58 the pore radii are expected to lie between 100 to 1000 nm. We have assumed a radius of 5 nm for our simulations unless otherwise stated, primarily due to computational limitations since the finite element mesh grows with R 2 .…”
Section: Gmpnp System Of Equationsmentioning
confidence: 99%
See 2 more Smart Citations